PEMBUKTIAN DAKWAAN PENUNTUT UMUM DALAM PERKARA USAHA PENAMBANGAN ILLEGAL DENGAN KETERANGAN AHLI PERTAMBANGAN - Fino Hartra, Atiah Ayuni (GEMA, 2015)
This study examines and answer the problems regarding the suitability of matter of illegal mining effort by presenting mining expert at the trial of the District Court Pacitan with provisions KUHAP. As for further study on mining expert evidence in illegal mining case examination considered by District Court Judge Pacitan.This research includes the doctrinal law study or prescriptive normative. Legal materials collection techniques in this study is the literature study, conducted by reading and studying the contents of primary legal materials and secondary legal materials from literature study to collect and collate the law writing relating to the study problem. Legal materials that have been collected and analyzed by case approach. Based on this type research, then the analysis techniques of legal materials used the deduction method syllogism to formulate legal facts by making conclusion on major and minor premise. Based on the study results can be concluded that the prosecutor in the case of attesting his illegal mining business in the expert on trial in state court pacitan has been in accordance with the provisions of the expert KUHAP mining expert testimony in the case investigation is considered illegal mining by Pacitan District Court Judge, District Court Judge consideration Pacitan in assessing the expert testimony in the case investigation of illegal mining is the expert testimony has a the strength of evidence free or virj bewijskracht.